Cameroon publications in the Science Citation Index Expanded: Bibliometric analysis - Tchuifon Tchuifon, Donald Raoul (2017)
Cameroon is one of the six countries of Central Africa with more than 20 000 000 residents. To characterize the Cameroon research performance, Cameroonians publications in the Science Citation Index Expanded during the period of 1936-2015, indexed in the Thomson Reuters SCI-EXPANDED database, were studied in this work. All documents of that period with Cameroon in the address field were included in the study. The document type, language, trend and collaborations were analyzed, as well as the output of different subject categories. Performances of countries, institutions and authors, including total, single, collaborative, first author, and corresponding author publications were also analyzed. Articles were analyzed by the scientific output and research performances of individuals, institutions and collaborative countries with Cameroon. Analyses included 8 457 articles (85 % of 10 591 Cameroonian publications). These bibliometric analyses of Cameroonian publications provided interesting insights concerning authors, institutions and collaboration patterns. Results showed that research in Cameroon was highly dependent on foreign collaborations, and the international collaboration was responsible for the increasing number of publications over the years. It was found that the articles with either first authors or corresponding authors from outside Cameroon got more citations than the others, and that the articles without any international collaboration had lower citations. The number of articles indexed by SCI-EXPANDED has seen an increase in terms of Cameroonian articles that is considerably greater that the increase in number of all articles in SCI-EXPANDED. Articles were more frequent than other types of publication and they were mostly in English. The University of Yaoundé I ranked top one in inter-institutionally collaborative articles, the rank of the total inter-institutionally collaborative articles, and the rank of first author articles and corresponding author articles. The University of Yaoundé I also was in an absolute leading position from 1970s to 2015, followed far away by the other institutions. The categories of tropical medicine, plant sciences, environmental and occupational public health, and infectious diseases, represented the largest number of published articles. Even though physics and chemistry dominated the ranking of the top 20 best Cameroonian authors, an independent mathematics article was the most cited, with 60 citations in 2015 to a Cameroonian author. The top three productive researchers were T. C. Kofane, B. T. Ngadjui, P. Woafo, all from University of Yaoundé I. France and the USA dominated the ranking of countries with strong scientific collaboration with Cameroon.